2021
DOI: 10.1186/s13019-021-01492-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tricuspid regurgitation on late right ventricular failure in left ventricular assist device patients ~can prophylactic tricuspid annuloplasty prevent late right ventricular failure? ~

Abstract: Background In this study, we evaluated the prevalence of tricuspid regurgitation (TR) worsening in patients with left ventricular assist devices (LVADs) and its impact on late right ventricular (RV) failure. Methods We enrolled 147 patients of the 184 patients who underwent continuous-flow LVAD implantations from 2005 to March 2018. The prevalence of postoperative TR worsening and late RV failure were retrospectively evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…22 However, a recent study stated that late RV failure cannot be prevented by concomitant TVS. 9 Further, in unmatched patients of a study with 3,323 participants by Veen et al, 16 there were increased incidences of RVF and temporary RVAD support in patients with concomitant TVS compared with patients without this additional procedure. Besides, a significantly increased cumulative incidence of RVF during follow-up was observed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…22 However, a recent study stated that late RV failure cannot be prevented by concomitant TVS. 9 Further, in unmatched patients of a study with 3,323 participants by Veen et al, 16 there were increased incidences of RVF and temporary RVAD support in patients with concomitant TVS compared with patients without this additional procedure. Besides, a significantly increased cumulative incidence of RVF during follow-up was observed.…”
Section: Discussionmentioning
confidence: 95%
“…6,7 The expected benefit of any concomitant tricuspid valve surgery (TVS) is based on the fact that (uncorrected) TR may aggravate the progress of the disease. 4,8,9 In a recent meta-analysis, though the pooled results failed to detect significant differences in interested outcomes, the authors concluded that concomitant TVS may benefit patients undergoing LVAD implantation since these patients had worse baseline characteristics. 10 Besides, current guidelines suggested considering concomitant TVS with LVAD implantation for moderate or worse regurgitation (classes of recommendations: IIb and levels of evidence: C).…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is still controversial and largely debated. Recent studies, including one randomized clinical trial-the TVVAD trial (NCT03775759) -, found that concurrent tricuspid valve repair at the time of LVAD implantation does not appear to lower the incidence of right heart failure (40)(41)(42).…”
Section: Tricuspid Valvementioning
confidence: 99%
“…While persistent MR after LVAD is a consistent marker of progressive RV failure ( 26 ), residual TR is not ( 27 ). In our experience the prevalence of significant residual MR after LVAD is similar between the groups with insignificant and significant TR, suggesting residual left sided failure is not the only etiology.…”
Section: Is It the Tricuspid Valve… Are We Measuring The Wrong Thing?mentioning
confidence: 99%
“…Intervention on the tricuspid valve at the time of LVAD has never demonstrated a survival advantage and concomitant TV procedures are associated with increased morbidity and mortality in a stratified analysis of the INTERMACS database ( 12 ). While concomitant TV surgery has been demonstrated to improve LVAD filling and hemodynamics ( 15 ), tricuspid annuloplasty does not impact the incidence or progression of late RV failure ( 27 ). Concomitant tricuspid surgery has a significant fail rate ( 14 ) and a small but persistent subset of patients (10–15%) without pre-operative TR develop TR over time ( 8 ).…”
Section: What We Think We Knowmentioning
confidence: 99%